Effect of α-Tocopherol Supplementation in Rooster Semen on Sperm Quality Parameters during in-Vitro Storage at 4°C - Mavi, Gurjot Kaur; Dubey, Prem Parkash; Sahoo, Saroj Kumar; Grewal, Ravinder Singh (The Indian Journal of Animal Reproduction, 2022)
The purpose of this study was to evaluate the probable effects of the α-tocopherol (Vitamin E) addition in different levels to the Tris based egg yolk plasma (T-EYP) extender in semen of Rhode Island Red roosters on spermatozoa quality during storage of semen at 4°C for 0, 24,48 and 72h. The collected semen from roosters was mixed together and extended with T-EYP. The extended pooled semen was divided into 5 treatments (T). T1 was a control group without any vitamin E addition. For T2 to T5 groups 0.5%, 1%, 2% and 3% vitamin E (w/v) was added respectively. Treatments were evaluated for sperm motility, sperm viability, morphological defect, membrane integrity and acrosome integrity after 0, 24, 48 and 72 h of incubation at 4°C. The evaluations of spermatozoa immediately after semen collection, revealed no significant differences among values the treatment groups, whereas after incubating the treatments for different spans of time, the sperm progressive motility and viability rates for groups supplemented with vitamin E were significantly (P
Keywords: Chilled Semen; α-Tocopherol; RIR breed; Sperm Attributes